The GIRK1 subunit potentiates G protein activation of cardiac GIRK1/4 hetero-tetramers - Kouki K Touhara; Weiwei Wang; Roderick MacKinnon (eLife, 2016)
G protein gated inward rectifier potassium (GIRK) channels are gated by direct binding of G protein beta-gamma subunits (Gβγ), signaling lipids, and intracellular Na+. In cardiac pacemaker cells, hetero-tetramer GIRK1/4 channels and homo-tetramer GIRK4 channels play a central role in parasympathetic slowing of heart rate. It is known that the Na+ binding site of the GIRK1 subunit is defective, but the functional difference between GIRK1/4 hetero-tetramers and GIRK4 homo-tetramers remains unclear. Here, using purified proteins and the lipid bilayer system, we characterize Gβγ and Na+ regulation of GIRK1/4 hetero-tetramers and GIRK4 homo-tetramers. We find in GIRK4 homo-tetramers that Na+ binding increases Gβγ affinity and thereby increases the GIRK4 responsiveness to G protein stimulation. GIRK1/4 hetero-tetramers are not activated by Na+, but rather are in a permanent state of high responsiveness to Gβγ, suggesting that the GIRK1 subunit functions like a GIRK4 subunit with Na+ permanently bound.